Letter to the Editor in response to “Single sural nerve response: A reliable and practical method for diagnosis of diabetic peripheral neuropathy in children with type 1 diabetes” - Muhammad Ibrahim (Journal of Diabetes Investigation)
The study by Şenol et al. highlights the utility of single sural nerve response assessment as a reliable and practical method for diagnosing diabetic peripheral neuropathy (DPN) in children with type 1 diabetes. We discuss the clinical significance of their findings, emphasizing the need for longitudinal studies and the potential benefits of integrating point‐of‐care nerve conduction devices for early detection. Future research should explore broader applications and cost‐effectiveness to enhance routine clinical practice.